DEVICE FOR CALIBRATION OF THE PRESSURE SENSOR OF GRANULAR BULK MATERIALS - A. Zhdanov; V. Petrov; Y. Misko (Zernovì Produkti ì Kombìkorma)
According to the plan for the implementation of the scientific and technical work "Experimental and theoretical studies of the influence of the roll of a vertical deep container on the distribution of horizontal pressure of granular bulk material on the walls of the container" (DR No. 0121U112518), which is being carried out at the Department of Mechanical Engineering of ODABA, for further research on the pressure distribution of bulk material, a pneumatic measuring system for measuring pressure of granular material on the vertical walls of storage models was developed. Pressure measurements are indirect - based on the absolute value of the movement of the sensor platform, which perceives the pressure of the bulk material, relative to the sensor body, the amount of pressure of the bulk material on the sensor was estimated. The system is multi-channel, each measuring channel consists of a bulk material pressure sensor, a channel for measuring movement of the pressure sensor platform and a recorder of this movement. The device for calibrating the pressure sensor is designed to obtain the calibration dependence of the output signal (the air pressure in the measurement chamber with pneumatic sieves) from the input signal (the value of the uniformly distributed pressure on the sensor). The device is two connected hydraulic systems filled with water. One of them consists of a pressure chamber with a flexible membrane through which the water pressure is transmitted to the sensor, and a measuring tube with a ruler to measure the water level above the membrane. The second one is a buffer tank for water, connected to the pressure chamber of the first system by a flexible tube and can move in vertical position. Hydrosystems are interconnected, so the both of them have the same water level. The water pressure on the sensor changes by moving the buffer tank up and down. The sensor is made in accordance with the patent of Ukraine for the invention and consists of a housing connected through an annular elastic element to the sensor platform, which perceives the pressure of the bulk material. In order to exclude the impact on the measured pressure by arching in the loose material above the sensor platform, linear displacements of the sensor platform relative to the housing should not exceed 5-8 ?m. Such small movements are measured by a non-contact pneumatic gauge based on a non-differential measuring pneumatic system of the manometric type with a working air pressure in the system of 7.5-10 kPa. Air pressure in the pneumatic system is measured by alcohol manometers. The device is made in the form of a two-branch rack: one branch is a measuring branch, and the other has a screw mechanism for vertical movement of the buffer tank. The accuracy of the pressure assignment on the sensor is ± 0.1 g/cm2, and the measurement of the output signal is ± 0.5 mm